How reliable are our beta-source calibrations? - Tribolo, Chantal; Kreutzer, Sebastian; Mercier, Norbert (Ancient TL, 2019)
The calibration of any artificial β-source attached to a luminescence reader is fundamental for the accuracy of luminescence dating results. Here, we present calibration results obtained for a β-source attached to a single grain Risø reader in Bordeaux using a series of quartz of different origins. The quartz was irradiated with three different γ-irradiators. An unexpected variability of the apparent dose rates was observed and our results suggest that the γ-irradiation is the main reason for this variability. Further work is needed to clarify the underlying reasons.